Kearifan Lokal dalam Cerita Rakyat “Timun Mas” Sebagai Media Pengenalan Budaya dalam Pembelajaran BIPA - Zainy, Rafiqah; Dea, Ivana May; Tambunan, Silvia Yulandari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article discusses the role of local wisdom in Timun Mas folklore as a medium of cultural recognition in learning Indonesian for Foreign Speakers (BIPA). In the context of globalization and increasing human mobility, understanding local culture is very important, especially for those who study Indonesian. The purpose of this article is to explore the local wisdom values contained in the Timun Mas story and analyze its potential as a medium of cultural recognition in BIPA learning. This article also aims to provide a deeper understanding of how the Timun Mas story can be integrated into BIPA learning. Through the text analysis method of Timun Mas folktale and literature study, this article identifies cultural values such as loyalty, courage, and justice contained in the story.